Dokazovanje v davčnih zadevah - Podlipnik, Jernej (Javna uprava, 2017)
The responsibility for correctness of fact finding in tax matters lies both on the tax administration and on taxpayers. To fulfil his or her responsibility many obligations are imposed on the taxpayer, such as keeping the books, issuing the invoices, submitting tax returns etc. If the taxpayer complies with his or her responsibilities, tax authority must prove beyond reasonable doubt that taxpayer's returns are incorrect and that he or she should have stated higher revenues, turnover etc., but when it is demonstrated without reasonable doubt that he or she does not, tax authority is entitled to estimate the probable tax base, and the taxpayer can prove that the tax base was wrongly estimated (reversed burden of proof). This concept enables an appropriate balance between tax authority and taxpayer when dealing with proving. But this balance is diminished in the so called tax on unreported income where the reversal of tax burden happens although it is only presumed that the taxpayer has perhaps not reported all of his or her income in recent years. In these cases, taxpayers often find themselves in evidence distress and they lose the case just because they are unable to prove their statements (the tax authority decides on the basis of the burden of proof). So although in recent years the Slovenian Supreme Court has done a lot to provide constitutional proving standards in the tax law cases, it is likely that the evolution of jurisprudence has not been finished.
Keywords: cenitev davčne osnove; davčni postopek; davek od neprijavljenih dohodkov; davki; dokazni elementi; dokazovanje; estimation of tax base; evidence elements; pravica do dokaza; proving; tax; tax procedure; the right to evidence; the tax on unreported income